Control over a linear system up to a given Lyapunov function - Kozhametov, A. T.; Khusainov, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain control conditions for a linear system whose Lyapunov functions satisfy certain conditions.